OBSTRUCTION IN THE DISCOVERY OF NEW ANTIBIOTIC DRUGS: - Farjad Afzal; Asma Afzal; Sidra Manzoor (Journal of University Medical & Dental College, 2017)
ABSTRACT: After discovery of antibiotic in 1928, there are 100 of compounds, but after 1987 no new class had been discovered. Infectious diseases are third leading cause of deaths in US and second leading cause in whole world. Obstruction in the discovery of new drugs is multifactorial; one factor is that bringing new drug into market requires 800 million US dollars and 10 years, pharmaceuticals companies have to bear a large cost on research and adverse effects. Another factor that was identified is that current focus is on drugs that are used for chronic diseases. Drugs for chronic diseases are used for longer periods of time as compare to antibiotics that are used for five to fourteen days. Health professionals, community, patients, researchers, media, industry and government should come forward to remove all possible barriers in the discovery of new drugs.